Diagnostic value of contrast-enhanced CT for elbow joint disorders in dogs - Rohr, Bettina; Reese, Sven; Zöllner, Martin; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2025)
ObjectiveComputed tomography (CT) with intravenous contrast agents can provide additional diagnostic information. To our knowledge, no previous study has evaluated the role of contrast agents in CT imaging of the canine elbow joint. This study aimed to determine the diagnostic value of post-contrast imaging.MethodsA total of 326 elbow joints from 163 dogs with unilateral or bilateral lameness caused by elbow joint pathology were examined using radiography and CT, both with and without contrast agents. Diagnoses assessed from radiographs and CT scans in the bone window included primary diseases and periarticular osteophytes. Possible primary diseases included medial coronoid process disease (MCPD), ununited anconeal process (UAP), osteochondrosis dissecans (OCD), humeral intracondylar fissure/incomplete ossification of the humeral condyle (HIF/IOHC), epicondylar spur, caudal or medial calcified bodies. Contrast enhancement of the joint capsule and flexor muscles was evaluated in the soft tissue window. Elbow joints without pathological findings, lameness, or contrast enhancement served as controls (n = 21).ResultsAmong the 137 elbow joints showing contrast enhancement, 94 demonstrated enhancement limited to the joint capsule, 16 to the flexor muscles, and 27 to both joint structures. Epicondylar spurs were most strongly associated with flexor muscle enhancement, whereas medially located calcified bodies were not. Joint capsule enhancement was most frequently associated with periarticular osteophytes. Notably, elbows with flexor muscle involvement but no epicondylar spur or calcified bodies (n = 14) could only be detected through contrast-enhanced imaging.ConclusionA contrast agent could be administered during most CT scans of the elbow joint to ensure that no pathological changes are overlooked. Nevertheless, it is important to weigh the benefits for treatment and prognosis against the risks of administering a contrast agent to the patient.